Layered Superhydrophobic Meshes for Controlled Drug Release - Falde, Eric J. (J Control Release, 2015)
Layered superhydrophobic electrospun meshes composed of poly(ε-caprolactone) (PCL) and poly(glycerol monostearate-co-ε-caprolactone) (PGC-C18) are described as a local source of chemotherapeutic delivery. Specifically, the chemotherapeutic agent SN-38 is incorporated into a central ‘core’ layer, between two ‘shield’ layers of mesh without drug. This mesh is resistant to wetting of the surface and throughout the bulk due to the pronounced hydrophobicity imparted by the high roughness of a hydrophobic polymer, PGC-C18. In serum solution, these meshes exhibit slow initial drug release over 10 days corresponding to media infiltrating the shield layer, followed by steady release over >30 days, as the drug-loaded core layer is wetted. This sequence of events is supported by X-ray computed tomography imaging of a contrast agent solution infiltrating the mesh. In vitro cytotoxicity data collected with Lewis Lung Carcinoma (LLC) cells are consistent with this release profile, remaining cytotoxic for over 20 days, longer than the unlayered version. Finally, after subcutaneous implantation in rats, histology of meshes with and without drug demonstrated good integration and lack of adverse reaction over 28 days. The drug release rates, robust superhydrophobicity, in vitro cytotoxicity of SN-38 loaded meshes, and compatibility provide key design parameters for the development of an implantable chemotherapeutic-loaded device for the prevention of local lung cancer recurrence following surgical resection.